PEMBUNGAAN Eucalyptus occidentalis PADA PERPANJANGAN MASA PENYINARAN DAN PACLOBUTRAZOL - Rina Laksmi Hendrati (Jurnal Pemuliaan Tanaman Hutan, 2008)
Flowering stimulation were investigated to accelerate deployment of E. occidentalis. It was found that extended daylength (16-h) in juvenile plants stimulate flowers of very limited individuals/family with less number of buds than normal inflorescences. Extended daylength (16-h) promote flowering of most families from 2 year-old E. occidentalis plants. In combination with paclobutrazol (1 mg. a.i/mm), number of buds were doubled. Under 16-h daylength, juvenil plants were taller up to 25 weeks than under natural light but shorter for family 96-LM that produced more flowers than others. There were no height differences between 16-h daylength and in combination with paclobutrazol in 2-year old plants.